Neoplastic pericardial disease. Analysis of 26 patients - Soufen,Helena Nogueira (1999)
PURPOSE: To characterize patients with neoplastic pericardial disease diagnosed by clinical presentation, complementary test findings, and the histological type of tumor. METHODS: Twenty-six patients with neoplastic pericardial disease were retrospectively analyzed. RESULTS: Clinical manifestations and abnormalities in chest roentgenograms and electrocardiograms were frequent, but were not specific. Most patients underwent surgery. There was a high positivity of the pericardial biopsy when associated with the cytological analysis of the pericardial liquid used to determine the histological type of the tumor, particularly when the procedure was performed with the aid of pericardioscopy. CONCLUSION: The correct diagnosis of neoplastic pericardial disease involves suspicious but nonspecific findings during clinical examination and in screen tests. The suspicious findings must be confirmed through more invasive diagnostic approaches, in particular pericardioscopy with biopsy and cytological study.